Students’ Errors in Solving Mathematical Connection Problems on Quadrilateral Topics (Unnes Journal of Mathematics Education, 2022)
The mathematical connection ability is the ability to use the relationship of ideas in mathematics and apply mathematical ideas in contexts outside of mathematics so that’s important because it can provide opportunities for meaningful learning. The background of this study was the wrong way of students' thinking and understanding so that causing errors in solving mathematical connection problems. This study aims to describe students' errors in solving mathematical connection problems on quadrilateral topics based on the Polya’s stages. This type of study was descriptive research with a qualitative approach. The data collection technique was carried out by giving participants tests and then conducting interviews with selected participants. The participants in this study were six students in junior high school, consisting of one student in class VIII and five students in class IX. Based on the results, some participants made several types of errors on the quadrilateral topics. The errors made by the participants occurred at the stage of understanding the problem, developing a plan, and implementing the plan. Students have not been able to optimize the use of knowledge related to mathematical ideas, procedures, or facts from a quadrilateral.